The Potential for Undersea Mining - David Dekker; Raymond Binns (Berita Sedimentologi, 2000)
The deep sea floor offers new opportunities for minerals exploration. Recent discoveries of high-grade massive sulphide mineralization represent resources whose extent is still unknown. Ferro-manganese nodules formed on abyssal plains are of more modest grade, but very expensive in area. While it is likely that continental shelves may contain seafloor mineralization deeper than deposits already exploited in coastal areas by conventional dredging, the focus of this paper is the hydrothermal vents of island arc and back-arc areas and the abyssal plains of the deep sea. These hold promise of ore deposits quite different from those known of land. Environmental advantages in mining the sea floor include no impact on the surface environment and in some cases opportunities for disposal of tailings back on the seafloor.